(untitled) (Iraqi Journal of Market Research and Consumer Protection, 2026)
A field experiment was conducted using five in bred lines of maize: NADH 102, NASA 2022, NAEL 2022, NA 9928 E, and NADH 2006, (numberd 1,2,3,4,5 respectively) In the first season of spring 2022, a half-diallel Crossing program was employed to obtain (10) single crossing hybrids. Subsequently, the parents and single cross hybrids were planted in two comparison experiment in the fields of the College of Agricultural Engineering Sciences - University of Baghdad / Jadriyah during the spring and fall seasons of 2023, following a RCBD design with four replications. To study the traits days to silking, ear height, leaf area index (LAI), ear length, days to physiological maturity (DTM), crop growth rate (CGR), ear weight, total dry matter (TDM), yield per unit area, and harvest index (HI). The results of the study showed significant differences between the genotypes, parent 1 recorded the highest yield per unit area, at 15.45 and 15.86 tons ha-1 for both seasons due to its superiority in CGR (6.32 and 6.54 g plant-1 day-1) for both seasons, as well as the highest ear weight (356.8 and 366.0 g) and highest TDM (594.8 and 628.4 g), with no significant difference with parent 3, with yield per unit area of 13.86 and 14.95 tons ha-1 for the two seasons, respectively. Due to its superiority in LAI, ear weight, and HI. Among the hybrids, the single cross hybrid (4×2) excelled with the highest yield, at 22.8 and 24.0 tons ha-1 due to its superiority in ear height (136.7 and 130.3) and highest TDM (697.0 and 672.8 g) for the two consecutive seasons. There is no significant difference between hybrid (2×4), and hybrid (1×5) with a yield of 22.7 and 23.1tons ha-1 for the two seasons, respectively, due to its early silking, DTM, and HI. We suggest studying single cross hybrids at different planting dates to demonstrate their ability to adapt to the Iraqi climate and test them under stress conditions such as drought and salinity.